PARAMEDICS ARE COLLABORATING WITH HEALTHCARE PROVIDERS TO OFFER MOBILE INTEGRATED HEALTHCARE SERVICES - Abdullah Ali Abdullah Alsahli, Ibrahim Saeed Mohammed Alahmari, Omar Abdulaziz Hamed Alghamdi (Chelonian Research Foundation, 2024)
This essay explores the growing trend of paramedics collaborating with healthcare providers to offer mobile integrated healthcare services at the Master level. The essay discusses the rationale for this collaboration, the methodology used to implement these services, the results achieved, and the implications for the future of healthcare delivery. Additionally, the essay highlights the importance of this collaboration in providing more comprehensive care to patients and improving overall health outcomes.